2020
DOI: 10.3390/antiox9050404
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Selected Antioxidants in Two Courgette Varieties from Organic and Conventional Production

Abstract: Courgette is considered as a low-calorie vegetable with health-promoting properties. However, scientific publications focused on the profile and content of bioactive compounds in courgette, as well as the potential fruit quality modulating factors, are rare. Due to the high adaptability of courgette to weather and agronomic conditions, it is produced on a global scale. The aim of this study was to analyse the impact of organic versus conventional agronomic practices on the concentration of selected antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
17
0
2
Order By: Relevance
“…Consequently, organic and low-input farming systems of cucurbit crops, where fertilisers are of natural origin, were able to increase the level of antioxidants in comparison with conventional farming systems. Thus, Kopczyńska et al [168] found that under organic conditions, zucchini fruits had higher antioxidant contents, specifically phenolic acids. Similarly, melon organic production enhanced fruit antioxidant contents compared with conventional production [77].…”
Section: Farming Systemmentioning
confidence: 99%
“…Consequently, organic and low-input farming systems of cucurbit crops, where fertilisers are of natural origin, were able to increase the level of antioxidants in comparison with conventional farming systems. Thus, Kopczyńska et al [168] found that under organic conditions, zucchini fruits had higher antioxidant contents, specifically phenolic acids. Similarly, melon organic production enhanced fruit antioxidant contents compared with conventional production [77].…”
Section: Farming Systemmentioning
confidence: 99%
“…The chromatographic peaks corresponding to particular carotenoids were identified by comparing the retention times with those of authentic standards (Fluka and Sigma-Aldrich, Poznań, Poland, purity of 99.98%). This methodology was previously described by Kopczyńska et al [19].…”
Section: Carotenoids Extraction and Identificationmentioning
confidence: 99%
“…The concentrations of polyphenols were calculated based on standard curve and sample dilution coefficients. This methodology was previously described in the study of Kopczyńska et al [19].…”
Section: Phenolics Extraction and Identificationmentioning
confidence: 99%
“…Algo a ser levado em consideração quando se fala em fatores de interferência para a disponibilidade de compostos fenólicos, é que no cultivo orgânico os alimentos estão muito mais expostos a fatores de estresse e com isso necessitam expressar algum tipo de defesa, a qual se caracteriza como uma maior produção de compostos bioativos como os polifenóis, caracterizando um aumento no poder antioxidante desses alimentos (23). Na literatura, alguns estudos têm mostrado que frutas orgânicas possuem um poder antioxidante maior e também uma quantidade significativa maior de polifenóis quando comparadas às convencionais (22,24,27), onde o cultivo orgânico parece ser mais influente na modulação de polifenóis das frutas analisadas. Neste estudo observou-se que a maior parte das frutas orgânicas apresentou valores superiores de polifenóis quando comparadas às convencionais.…”
Section: Teor De Polifenóis (Solúveis E Hidrolisáveis) Em Frutas Orgânicas E Convencionaisunclassified